Identifying Technological Potentials - Penning de Vries, Frits W. T.; de Wit, Cornelis T. (International Food Policy Research Institute, 1987)
The potential for food production in sub-Saharan Africa far exceeds current production. Low soil fertility is among the principal causes of low yields. Intensification of agriculture and further expansion of the cropped area requires more external inputs, which often are not available to the rural farmer or are too expensive. As a result, yields per unit area are not increasing, area expansion occurs slowly, and food production grows at a slower rate than the population.